PENGARUH LEVEL BOKASHI KOTORAN AYAM TERHADAP PERTUMBUHAN VEGETATIF SORGUM BROWN MIDRIB (BMR) PADA KONDISI TERNAUNG - Rawung, Claudia F.; Anis, S.D; ., Rustandi; Kaunang, W.B. (Universitas Sam Ratulangi, 2018)
THE INFLUENCE CHICKEN MANURE BOKASHI ON VEGETATIVE GROWTH OF BROWN MIDRIB SORGHUM (BMR) UNDER SHADE. The aim of this experiment was to study the effects of application of chicken manure bokashi on the vegetative growth of Brown Midrib (BMR) sorghum. Completely Randomized Design (CRD) has been used according to Steel and Torrie (1995). The treatments were level of chicken manure bokashi as follows B1= 0 gram; B2= 200 gram; B3= 400 gram and B4= 800 gram/polybag, with 7 replications to form 28 numbers of observations. The variables measured were plant height, leaf number and length of leaf. Analysis of Variance showed that treatments effected significanly different (P<0.05) on plant height, leaf number and length of leaf. Result of Tuckey Simultenaus Test showed that between treatment B3 and B4 were not significant different (P>0.05) on all variable measured, but both treatments gave a good performance of all variable measured significantly (P<0,05) better than treatments B2 and B1. Based on this research result it can be concluded that utilization of chicken manure bokashi up to 400 gram/polybag could provide nutrients requirement to support vegetative growth of sorghum BMR in term of height of plant, leaf number and length of leaf. Keywords: Bokashi, chicken manure, growth, BMR sorghum, shaded.